Debris Flows and Water Tracks in Continental Antarctica: Water as a geomorphic agent in a hyperarid polar desert - Hauber, Ernst; Sassenroth, C.; de Vera, Jean Pierre Paul; Schmitz, N.; Reiss, Dennis; Hiesinger, H.; Johnsson, Andreas (2017)
Most studies using Antarctica as a Mars analogue have focused on the McMurdo Dry Valleys, which are among the coldest and driest places on Earth. However, other ice-free areas in continental Antarctica also display landforms that can inform the study of the possible geomorphic impact of water in a polar desert. Here we present a new analogue site in the interior of the Transantarctic Mountains in Northern Victoria Land. Gullies show unambiguous evidence for debris flows, and water tracks act as shallow subsurface pathways of water on top of the permafrost tale. Both processes are driven by meltwater from glacier ice and snow in an environment which never experiences rainfall and in which the air temperatures probably never exceed 0°C.